Migration, mujercitas, and medicine men : living in urban Mexico - Napolitano, Valentina (University of California Press, 2002)
Exploring issues of migration, medicine, religion, and gender, this work analyses everyday practices of urban living in Guadalajara, Mexico. Drawing on fieldwork over a ten-year period, Velentina Napolitano paints a vibrant picture of daily life in a low-income neighbourhood of Guadalajara.